Tentoonstelling "Made in Belgium". (Brussel : Economisch en Sociaal Instituut voor de Middenstand, 1987)
Doise, Jozefa ; Szaraz, Marika ; Verhoeven, Ann ; Bataille, Marie-Henriette ; De Cleyn, Peter ; Frerar, Géo ; Meertens, Carla ; Muys, Herman ; Stockmans, Piet ; Tinck, Lucien ; Vandeghinste, Lucas ; Vander Elst, Jan ; Van Houtte, Lode ; Vermoere, Gerda ; etc.
Tentoonstelling "Made in Belgium", Heizel, Brussel, 9 - 13 decelber 1987
boek